Factores de riesgo para el rechazo de la vacunación para COVID19 de niños de 5 a 11 años en Loreto, 2022 - Montero Vasquez, Klellyha Llerme (2023)
Objective: Determine the risk factors for the rejection of vaccination for COVID19 in children from 5 to 11 years of age in Loreto 2022. Methods: A quantitative, descriptive, cross-sectional and prospective study was carried out. Results: 314 children from 5 to 11 years of age distributed proportionally between Maynas and Loreto Nauta were analyzed, where 216 children do not have any dose, and 98 children have at least a single dose for COVID19. It was found significantly that the child does not have any dose or at least a single dose for COVID19, such as socioeconomic factors, the age of the father or caregiver, older than 35 years (p 0.02), who belong to the Christian religion / evangelical (p 0.02). As operational factors, parents or caregivers who do not consider the vaccine necessary are associated (p<0.0001). As cultural factors are associated, parents or caregivers express that they have no reason to vaccinate or complete their child's dose (p <0.0001). Conclusions: The risk factors are the age of the child's parent or caregiver over 35 years of age, belonging to the Christian/Evangelical religion, parents or caregivers who do not consider the vaccine necessary, and those who express that they have no reason to vaccinate or complete the vaccination. dose of your child, are significantly related to the rejection of the vaccine for COVID19.